The 2009-2011 United States-China Dispute on Increasing Import Tariffs on Chinese Tires - Angga Aditama Putra (Journal of World Trade Studies, 2013)
The China-United States tire dispute was the first case concerning the China-specific Safeguard, particularly China's Accession Protocol and Section 421 of the Trade Act 1974. The China-specific Safeguard was implemented by the United States to block products solely from China to enter the US market. This article questions China's decision to countermeasure the US tire tariff policy under the WTO and the nature of special safeguards as a means of protectionism. This article also examines the characteristics of the China-specific Safeguard, which is easier to implement than traditional safeguard measures. Additionally it analyses the effect of the US tire tariff policy on China's domestic tire industry and export. Tariffs imposed by the United States are considered as a threat to the development of China's domestic tire industry both in the process of imposing safeguards and the policy's effect The US victory in the tire tariff dispute shows that the China-specific Safeguard can be used to exceed the rationality of the WTO's traditional safeguard measures. It also illustrates that the WTO has not been able to overcome the protectionist measures implemented by its members.